2019
DOI: 10.1177/0022034519858063
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the STAT1 Pathway Accelerates Periodontitis inNos3-/-Mice

Abstract: Early studies on the etiology and pathogenesis of hypertension have shown that it has a considerable association with inflammation and the immune response as well as periodontitis. Clinical studies have also shown that hypertension can promote the periodontal tissue destruction caused by periodontitis. However, the underlying mechanisms remain unclear. This study aimed to explore the possible mechanisms of how hypertension aggravates periodontitis. Treatment with or without the signal transducer and activator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
0
19
1
Order By: Relevance
“…38 In this study, after inhibiting STAT1 signalling with fludarabine, macrophages were found to display decreased HK2 expression and thus, impaired glycolysis and inflammatory cytokine release. Although a report showed that fludarabine is not a specific inhibitor of STAT1, 61 our data in Figure 5E indicate that Tim-3 signalling inhibits STAT1 induced HK2 expression. These data suggest that STAT1 plays a role in Tim-3-mediated regulation of glycolysis and inflammatory responses.…”
Section: Discussioncontrasting
confidence: 84%
“…38 In this study, after inhibiting STAT1 signalling with fludarabine, macrophages were found to display decreased HK2 expression and thus, impaired glycolysis and inflammatory cytokine release. Although a report showed that fludarabine is not a specific inhibitor of STAT1, 61 our data in Figure 5E indicate that Tim-3 signalling inhibits STAT1 induced HK2 expression. These data suggest that STAT1 plays a role in Tim-3-mediated regulation of glycolysis and inflammatory responses.…”
Section: Discussioncontrasting
confidence: 84%
“…IRF8 can then promote the activation of the downstream TLR pathway and produce various pro-inflammatory factors such as TNF-a and IL-1b [29]. Wei et al found that inhibiting STAT1 decreased macrophage infiltration and the production of inflammatory cytokines [18].…”
Section: Discussionmentioning
confidence: 99%
“… 48 However, STAT3 activation is also indispensable for anti-inflammatory processes, such as IL-10 receptor signalling. 49 , 50 Due to the mitigating effect of iPTH on inflammatory bone loss observed in this study, we inferred that STAT3 may play an anti-inflammatory role in the mechanism by which iPTH preserves bone mass.…”
Section: Discussionmentioning
confidence: 65%